Can Volumetric and Morphological Variants of Sphenoid Sinuses Influence Sinuses Opacification?. Issue 8 (November 2018) - Gibelli, Daniele Maria; Cellina, Michaela; Gibelli, Stefano; Schiavo, Paolo; Oliva, Antonio Giancarlo; Termine, Giovanni; Ferrario, Virgilio F.; Dolci, Claudia; Sforza, Chiarella
Abstract : Abstract: Improvements in computed tomography and in functional endoscopic sinus surgery have recently increased interest toward paranasal sinus anatomy and anatomic variations that can be observed in patients affected by sinusitis. Isolated sphenoid sinusitis is a relatively rare pathology, often related to nonspecific symptoms, therefore making diagnosis difficult. The correlation between this type of sinusitis and anatomical variants remains unclear. The authors' aim was to retrospectively revise paranasal sinuses computed tomography scans of patients affected by sphenoid sinusitis, compared with a control group, analyzing the types of sphenoid sinus and the presence of aberrant pneumatization, and performing a segmentation of the sphenoid sinuses to calculate the volumes. Sphenoid sinuses of 60 patients affected by sinus opacification, compared with a control group, were segmented. Type of sinus (sellar, presellar, postsellar) and presence of aberrant pneumatization were assessed as well. Possible statistically significant differences in volumes according to sex and group were assessed through 2-way ANOVA test ( P  < 0.05). Post-hoc test was assessed through Student t test. χ 2 test was applied in order to verify the statistically significance of differences in frequency of different types of sinus pneumatization variants ( P  < 0.05). Average volume of sphenoid sinuses in males was of 7.672 cm 3 and of 7.751 cm 3 in females within the group of patients; statistically significant differences in volume were found according to sex ( P : 0.342), but not between the patients and control group ( P : 0.0929). Post-hoc test verified that males affected by sinus opacification showed smaller volumes in comparison with the control males ( P  < 0.05). In addition, patients by affected sinus opacification showed more frequently the postsellar type and were less affected by pneumatization variants of the sphenoid bone than the control group ( P  < 0.05). This study first suggests the possible protective role of variants of pneumatization in the development of sphenoid sinus opacification.